Safety standards in anesthesiology and during regional anesthesia: implementation in Ukraine - Bielka, K. Yu.; Kuchyn, Yu. L.; Semenko, N. M. (Zaporozhye Medical Journal, 2023)
Patient safety in surgical settings is an integral part of the further sustainable development of medicine in Ukraine. This is key in times of the war and post-war state when the budget deficit at all levels of public administration and health care is significant and may grow significantly in the future. Medical errors during anesthetic management and surgery are particularly costly and significantly burden the health care system. Even the wealthiest economies cannot afford such mistakes. The price is particularly high for Ukrainian realities, and these mistakes are fatal for our health care. For this review, the authors used the electronic databases MEDLINE and Embase. 15 studies were included in the review. A part of the data was also included from the department research. Demonstration of own results is limited, as the data have already been published in other publications or materials are in the reviewing process. Basic monitoring according to the WHO standards / World Federation of Societies of Anesthesiologists (WFSA) is mainly used in hospitals of European Union countries. Results are close to 100 % for pulseoximetry and blood pressure, 98 % for electrocardiography, and 96 % for capnography. In Ukraine, monitoring methods do not have critical differences, except for a slightly lower (73.7 %) spread of capnography and ECG monitoring (83.4 %). The situation is less encouraging in the context of regional anesthesia. In Ukraine, the situation is much worse. According to the survey conducted by our department, ultrasound navigation is available in only 67 % of hospitals. There is also a low level of taking safety measures, which include checklists, training, and clinical analyzes of errors. Conclusions. According to the data of this literature review, the components of the Declaration of Helsinki on safety in anesthesiology are gradually being implemented in Ukraine, the use of the WHO checklist “Safe surgery” and safety standards of regional anesthesia is spreading. The main directions for further development are the education of physicians and other staff on patient safety, the approval of national standards and monitoring of their implementation in practice, the creation of a notification and audit system for complications and critical incidents during anesthesia.